A SEMIOTIC ANALYSIS OF JERIENG TRIBE'S SEDEKAH GUNUNG TRADITION - Fernanda, Andri; Ansyari, Irvan; Farhaby, Arthur Muhammad (University of Kuningan, 2025)
Myth is a story whose origin and author are unknown. The purpose of a Myth is to explain natural processes, the creation of the world, human races, traditional customs, political institutions, or religious rituals. In Pelangas Village, West Bangka, there is a tribe known as the Jerieng Tribe. This tribe has a tradition that is still practiced by its people, which the Sedekah Gunung tradition. This tradition is carried out every year to coincide with the 14th night full moon. Because the Sedekah Gunung ritual tradition is a traditional procession that cannot be separated from people's belief in myth, this research aims to analyze the representation of myth in the Sedekah Gunung ritual using semiotic theory by Charles Sanders Peirce. This research uses descriptive qualitative methods with data collection techniques in the form of a combination of interviews, observation, documentation. The results of this research found several ritual practices in Sedekah Gunung which symbolize the Jerieng Tribe's belief in the sacredness of the Sedekah Gunung ritual, belief in the myth of the symbiotic relationship between humans and nature through the practice of giving and receiving, as well as the respect and communication of the Jerieng Tribe towards nature through Sedekah Gunung.